CO2 Conversion by Combining a Copper Electrocatalyst and Wild‐type Microorganisms. Issue 15 (16th June 2020) - Chatzipanagiotou, Konstantina‐Roxani; Jourdin, Ludovic; Buisman, Cees J. N.; Strik, David P. B. T. B.; Bitter, Johannes H.
Abstract: Carbon dioxide (CO2 ) can be converted to valuable products using different catalysts, including metal or biological catalysts (e. g. microorganisms). Some products formed by metal electrocatalysts can be further utilized by microorganisms, and therefore catalytic cooperation can be envisioned. To prevent cumbersome separations, it is beneficial when both catalyst work under the same conditions, or at least in the same reaction medium. Here, we will show that a formate‐producing copper electrocatalyst can function in a biological medium. Furthermore, we will show that the effluent of the copper‐containing reactor can be used without purification as the sole medium for a bio‐reactor, inoculated with a mixed culture of microorganisms. In that second reactor, formate, H2 and CO2 are consumed by the microorganisms, forming acetate and methane. Compared to simple buffer electrolyte, catalytic activity of copper was improved in the presence of microbial growth medium, likely due to EDTA (Ethylenediaminetetraacetic acid) present in the latter. Abstract : This paper explores the feasibility of combining metal and biological catalysts for CO2 conversion. Microbial medium electrolyte enhanced formate production with a copper electrocatalyst. Microorganisms grew in spent electrolyte and utilized this formate for biological processes. Thus, there is potential to combine the two types of catalysts for CO2 conversions.